2019
DOI: 10.21684/2412-2343-2019-6-4-34-66
|View full text |Cite
|
Sign up to set email alerts
|

DISMISSAL PROTECTION IN THE BRICS COUNTRIES IN LIGHT OF ILO CON VENTION No. 158

Abstract: The BRICS countries have aspirations to achieve sustainable development in their economies and environmental protection. These aspirations have an important social aspect in the area of employment protection as it relates to ensuring fair development. In order to establish national standards for dismissal protection in four of the BRICS countries (Brazil, Russia, China and South Africa) the authors have considered the legislation and relevant national case law. This paper includes a review of International Lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Moreover, it is found that the situation in policing departments of South Africa is no better (Workman-Stark, 2015;Khosa, 2021). Additionally, it is also confirmed that there are a number of acts that are passed in the South Africa for ensuring equitable opportunities in the workplace to women (Vyas-Doorgapersad and Bangani, 2020;Sychenko, Laruccia, Cusciano and Chikireva, Wenpei and Smit, 2019;Prenzler and Sinclair, 2013), but there is only one bill that is passed for ensuring their empowerment (Republic of South Africa, 2013;Hills, 2015). It can also be elucidated that there is still a lack of evidence on the challenges that are faced by women in policing departments and thereby, men's perception towards women colleagues.…”
Section: Empirical Literaturementioning
confidence: 94%
“…Moreover, it is found that the situation in policing departments of South Africa is no better (Workman-Stark, 2015;Khosa, 2021). Additionally, it is also confirmed that there are a number of acts that are passed in the South Africa for ensuring equitable opportunities in the workplace to women (Vyas-Doorgapersad and Bangani, 2020;Sychenko, Laruccia, Cusciano and Chikireva, Wenpei and Smit, 2019;Prenzler and Sinclair, 2013), but there is only one bill that is passed for ensuring their empowerment (Republic of South Africa, 2013;Hills, 2015). It can also be elucidated that there is still a lack of evidence on the challenges that are faced by women in policing departments and thereby, men's perception towards women colleagues.…”
Section: Empirical Literaturementioning
confidence: 94%
“…Also, Section 186(1)(c)(i), under the LRA, 1995 prohibits employers from dismissing a willing employee from returning to their office after the period of maternity leave. Precisely, the LRA makes way for unfair dismissal (Sychenko et al 2019).…”
Section: Women Empowerment: Undertaken Initiatives South Africa Versu...mentioning
confidence: 99%